PREDICTABLE INTERPROXIMAL TISSUE REMOVAL WITH A SURGICAL STENT - Frizzera, Fausto; Pigossi, Suzane Cristina [UNESP]; Tonetto, Mateus Rodrigues; Kabbach, William; Marcantonio, Elcio [UNESP] (Elsevier B.V., 2014)
The correction of diastemas in the anterior region with composite resin is considered to be practical and conservative. Harmony between the restorative material and the periodontium is necessary to achieve satisfactory functional and esthetic results. Whenever excessive gingiva occurs in the interproximal region, removal is necessary to avoid excessively contoured restorations. A predictable technique is described to conservatively remove interproximal tissue in situations in which crown lengthening is required to treat bilateral diastemas. A surgical template based on the diagnostically waxed cast was produced to serve as a reference during periodontal surgery.